Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How to deduce formula for $\operatorname{arcsinh}(x)$ knowing that $\sinh(x)=\dfrac{e^x-e^{-x}}{2}$, $\sinh'(x)=\cosh x$ and $(f^{-1}(x))'=\dfrac{1}{f'(f^{-1}(x))}$ ?

share|improve this question
2  
Did you even try anything? All you need is given, so if you had just plugged in everything in that last formula you would have obtained the result yourself. –  TMM Mar 11 '12 at 15:19
    
I do not understand your indignation. I've tried, but I couldn't. I've explained in my comment under the answer which fragment I don't understand.. –  xan Mar 11 '12 at 15:24
    
If Alex had answered simply $\mathrm{arcsinh}'(x) = \frac{1}{\sqrt{x^2 + 1}}$, would it have helped you? You want others to explain what they did, so the least we can ask is you to do the same. –  TMM Mar 11 '12 at 15:32
    
Ok, in future I will think twice before I ask, but nobody yelled at me because of my questions before, so I didn't realise that.. –  xan Mar 11 '12 at 15:50
add comment

2 Answers 2

up vote 5 down vote accepted

Yes. Letting $f(x)=\sinh(x)$ we have $f'(x)=\frac{e^x+e^{-x}}{2}=\cosh(x)$ thus $$(f^{-1}(x))'=\frac{1}{f'(f^{-1}(x))}=\frac{1}{\cosh(\mathrm{arcsinh}(x))}=\frac{1}{\sqrt{x^2+1}}.$$

It is worth noting that the formula $(f^{-1}(x))'=\frac{1}{f'(f^{-1}(x))}$ comes from the chain rule, as $$1=\frac{d}{dx} x=\frac{d}{dx}f(f^{-1}(x))=f'(f^{-1}(x))(f^{-1}(x))'$$ so rearranging gives the desired result.

share|improve this answer
    
I don't understand this: $\frac{1}{\cosh(\mathrm{arcsinh}(x))}=\frac{1}{\sqrt{x^2+1}}$ Where it came from? –  xan Mar 11 '12 at 15:21
    
@xan: It comes from $\cosh^2 w-\sinh^2 w=1$, which can be verified directly from the definition of $\cosh$ and $\sinh$. –  André Nicolas Mar 11 '12 at 15:32
    
now I understand everything, thank you :-) –  xan Mar 11 '12 at 15:46
add comment

To find $$y=\operatorname{arcsinh} x = \frac{e^x-e^{-x}}{2}$$ put $t= e^x$, which leads to an easy equation.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.